Adequacy of Food Availibility for Farming Households in Moving and Setting Field Agriculture Systems - Lobo, Anita Trisia Dimu; Lalel, Herianus J.D; Ratu, Jacob M (Universitas Djuanda, 2023)
An analysis of the food sufficiency of farming households in shifting and permanent farming systems in South Central Timor Regency, Tobu sub-district (Tobu Village and Tutem Village) and Fatumnasi sub-district (Fatumnasi Village and Kuanoel Village), villages directly bordering the Mutis nature reserve, was carried out in October - November 2018. The aim of this research is to analyze the adequacy of food availability in farming households through shifting cultivation systems and settled farming systems and to determine the diversity of plants in shifting cultivation systems and settled farming systems. This research was conducted using a survey method through direct observation in the field and interviews with people in shifting and permanent cultivation. Farming household data was taken from Fatumnasi sub-district (sedentary farming) and Tobu sub-district (moving farming) and carried out in a balanced manner (Proportionate Random Sampling). The results of diversity analysis in swidden and permanent farming households are categorized as moderate diversity (1 < H < 3), this is because there are few types of plants planted in the location.